Strategi Pencegahan Stunting Dengan Intervensi Kebijakan Publik Dan Intervensi Gizi: Systematic Literature Review - Sutiyono Sutiyono; Muhammad Makmun; Nurya Kumalasari (Indonesian Journal of Health Community, 2025)
Stunting is a serious public health problem globally, particularly in developing countries. The prevalence of stunting in 2024 is projected to be 21.6%, meaning that 1 in 5 children under five in Indonesia will experience chronic growth problems. The purpose of this study was to analyze the literature on stunting prevention through policy and nutrition interventions. This study used a systematic literature review approach. Data were obtained from databases such as PubMed, Scopus, Google Scholar, and Web of Science, as well as national policy documents. The analysis was conducted using a PRISMA diagram. The articles discussed stunting prevention with a focus on public policy and nutrition interventions. The analysis results were synthesized to identify patterns, effectiveness, and relationships between public policy and nutrition interventions on stunting prevention. Addressing these issues requires a combination of policy and nutrition interventions. Social protection policies, food aid, and local economic development can increase the consumption of nutritious food and accelerate stunting reduction. One effective approach is the use of spatial data.